2019
DOI: 10.3390/ijms20246168
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Ameliorates Ischemic-Hypoxic-Induced Neurotrophin Receptor p75 Upregulation in the Endothelial Cells of Neonatal Mouse Brains

Abstract: Ischemic stroke is a leading cause of human death in present times. Two phases of pathological impact occur during an ischemic stroke, namely, ischemia and reperfusion. Both periods include individual characteristic effects on cell injury and apoptosis. Moreover, these conditions can cause severe cell defects and harm the blood-brain barrier (BBB). Also, the BBB components are the major targets in ischemia-reperfusion injury. The BBB owes its enhanced protective roles to capillary endothelial cells, which main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…This cleavage event in turn results in generation of a pro-apoptotic intracellular domain as a result of intramembrane proteolysis [40,41]. Previous studies have shown that upregulation of p75NTR expression in retinas in experimental diabetes and in ischemia-reperfusion injury in the brain correlates with accelerated apoptotic death of endothelial cells [51,52]. Our data extend these findings by showing that IR-induced expression of the full-length p75NTR is also associated with increased generation of pro-apoptotic p75ICD fragment.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This cleavage event in turn results in generation of a pro-apoptotic intracellular domain as a result of intramembrane proteolysis [40,41]. Previous studies have shown that upregulation of p75NTR expression in retinas in experimental diabetes and in ischemia-reperfusion injury in the brain correlates with accelerated apoptotic death of endothelial cells [51,52]. Our data extend these findings by showing that IR-induced expression of the full-length p75NTR is also associated with increased generation of pro-apoptotic p75ICD fragment.…”
Section: Discussionsupporting
confidence: 85%
“…The contribution of ADAM17 to apoptotic cell death in the ischemic retina could also be attributed to its activity toward p75 neurotrophin receptor (p75NTR), which has been shown to be involved in regulation of survival and apoptosis of both neurons and endothelial cells [41,[49][50][51]. It was reported that the full-length p75NTR undergoes cleavage by ADAM17 to generate a soluble p75NTR extracellular domain [40].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kuo et al even showed that p75 NTR caused bEnd.3 endothelial cells apoptosis and tight junction degradation under OGD and reoxygen injury (Kuo et al, 2019). In addition, upregulated p75 NTR in neurons has been reported to cause neuronal apoptosis after stroke (Irmady et al, 2014;Jover et al, 2002;Park et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of NGFR (neurotrophin p75 receptor; p75 NTR ) in endothelial cell (EC) is up-regulated in type-1 diabetes and hindlimb ischemia under conditions where EC apoptosis is induced [ 16 ]. p75 NTR is up-regulated by ischemia–reperfusion injury and decreases the expression of tight junction proteins (ZO-1, claudin-5) in EC, leading to apoptosis [ 27 ]. Furthermore, microRNA-503 produced in a p75 NTR -dependent manner in EC is transferred to recipient pericytes, leading to reduced production of vascular endothelial growth factor and EC dysfunction [ 28 ].…”
Section: Discussionmentioning
confidence: 99%